Can undergraduate paramedic students accurately identify lung sounds?. Issue 8 (22nd July 2009) - Williams, B; Boyle, M; O'Meara, P
Abstract : Introduction: The accurate identification of lung sounds during chest auscultation is a skill commonly used by healthcare clinicians, including paramedics, when assessing a patient's respiratory status. It is a necessary skill as it enables confirmation of a patient's respiratory condition and guides the paramedic to a provisional diagnosis and the implementation of appropriate management. The object of this study was to identify if undergraduate paramedic students from two Australian universities were able to interpret a variety of lung sounds accurately. Methods: A prospective single-blinded observational study requiring 96 undergraduate paramedic students from two Australian universities to estimate the lung sounds of six audio files. Results: The findings demonstrated variable accuracy in lung sound interpretation of the six audio files. The lung sound that contained a wheeze was most accurately interpreted, whereas coarse crackles were the least accurately interpreted. Monash University undergraduate paramedic students displayed similar lung sound interpretations to Charles Sturt University undergraduate paramedic students. Conclusion: In this study undergraduate paramedic students from two Australian universities were found to be inaccurate at interpreting a variety of common lung sounds. The study has highlighted that a greater emphasis needs to be given to lung sound interpretation in undergraduate paramedic education programmes.